Some problems of research exploring sex differences in sport-related concussions: a narrative review - Malcolm, D. (Research in Sports Medicine, 2024)
This narrative review scrutinizes research exploring sex-based differences in experiences of sport-related concussion. The article argues that the limitations of epidemiological studies identifying the greater incidence and severity of concussion among females require that these findings are read with caution. It secondly argues that the dominant explanations for these data are based on and extend historical tendencies to "other" female participation in sport and construct male experiences as the "norm". Finally, the article critiques policy recommendations related to these research findings, arguing that they are likely to embed rather than challenge sex inequality in sport, and that they are both impractical and unethical. While this commentary builds on a broader body of work advocating greater sex/gender equality in sports science research, the prominence of social concerns about concussions in sport makes the broader implications of the focus on sex and sport-related concussion particularly problematic and thus in need of redress.